The Role of Photo Editing in Instagram Towards the Body Image Among Female Teenagers - Baiq Muthia Maharani; Bella Cita Nanda Hawa; Putri Tasya Devita (Department of Communications, Universitas Islam Indonesia, 2020)
The use of social media among teenagers, such as Instagram, has influenced how they perceive their own bodies. This study aimed to find out the role of photo editing among female teenagers in affecting their body image. The study has applied a descriptive qualitative approach. The data were collected through interviews with the selected informants, i.e. female teenagers in Yogyakarta, Indonesia, that using Instagram and photo editing applications, with a range of age 12-18 years old. This study finds that the most important motivation for sharing the photos is showing the best of body image according to certain socially constructed standards. Some teenagers have positive self-concept and are more confident in sharing their photos without any editing processes. While some others feel dissatisfaction with their body image, find insecure and afraid of negative comments, and in turn need to edit their photos before uploading to Instagram. Keywords: body image, female teenager, photo editing, insecure, Instagram.